1,3-butadiene synthesis catalyst and method for producing same, and method for producing 1,3-butadiene
Patent Information
- Application Number
- JP2023537867
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-07-29
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-07-29
AI Technical Summary
Current methods for synthesizing 1,3-butadiene from ethanol using conventional catalysts result in low yield, necessitating the development of a more efficient catalyst with dehydrogenation, Lewis acid, and mild Brønsted sites for improved conversion.
A catalyst comprising a porous silica carrier with crystalline silica, Zn, and Zr, featuring a multimodal pore size distribution and specific molar ratios, is developed, with ZnO supported on the silica and Zr interacting with silanol groups to form Lewis active centers, enhancing dehydrogenation and aldol condensation efficiency.
The catalyst significantly improves the yield and selectivity of 1,3-butadiene synthesis from ethanol, demonstrating enhanced stability and mass transfer efficiency due to its hierarchical structure and uniform active center dispersion.
Smart Images

Figure 00000015_0000 
Figure 00000016_0000 
Figure 00000017_0000
Abstract
Description
1,3-butadiene synthesis catalyst, its production method, and 1,3-butadiene production method
[0001] An embodiment of the present invention relates to a catalyst for synthesizing 1,3-butadiene from ethanol, a method for producing the catalyst, and a method for producing 1,3-butadiene using the catalyst.
[0002] 1,3-Butadiene is widely used as a raw material in the production of butadiene rubber (BR) and styrene-butadiene rubber (SBR). Currently, 1,3-butadiene is mainly produced by separating it from the C4 fraction during the production of ethylene by steam cracking naphtha. In recent years, there has been a demand for the synthesis of 1,3-butadiene from raw materials other than petroleum. As such an alternative method, a method for synthesizing 1,3-butadiene from ethanol by direct conversion has been proposed.
[0003] For example, Patent Document 1 discloses a catalyst for obtaining butadiene by contacting YO with ethanol. 2 and a catalyst comprising a zeolite material having a framework structure comprising: wherein at least a portion of Y contained in the framework structure is isomorphously substituted with element X. Here, Y is preferably Si, Sn, Ti, Zr, or Ge, and X is preferably Zr, Ti, Sn, or Ta. Patent Document 1 also discloses that a zeolite material in which Y is Si and X is Ti may further contain Zn as a non-framework element.
[0004] Patent Document 2 describes a catalyst for obtaining 1,3-butadiene from ethanol, which is obtained by kneading magnesium hydroxide, colloidal silica, zinc nitrate, and zirconium oxynitrate together with water and calcining the mixture (ZnO / ZrO 2 / MgO / SiO 2 ) has been disclosed.
[0005] WO2014 / 198901A1 WO2013 / 125389A1
[0006] The direct conversion of ethanol to 1,3-butadiene is a promising route. However, this direct conversion is a complex reaction and requires a multifunctional catalyst with dehydrogenation sites, Lewis acid sites, and mild Brønsted sites. However, conventional catalysts do not necessarily produce high yields of 1,3-butadiene, and there is a need to improve the yield.
[0007] An object of an embodiment of the present invention is to provide a catalyst for synthesizing 1,3-butadiene that can efficiently synthesize 1,3-butadiene from ethanol, a method for producing the same, and a method for producing ethanol using the catalyst.
[0008] The present invention includes the following embodiments: [1] A catalyst for synthesizing 1,3-butadiene from ethanol, comprising a porous silica support made of crystalline silica, Zn, and Zr, and having a first peak pore diameter (D micro ) and a second peak pore diameter (D meso+macro A catalyst for 1,3-butadiene synthesis having a multimodal pore size distribution including
[0009] [2] A catalyst containing a porous silica support made of crystalline silica, Zn, and Zr, and having a first peak pore diameter (D micro ) and a second peak pore diameter (D meso+macro 1,3-butadiene from ethanol in the presence of the catalyst having a multimodal pore size distribution containing
[0010] [3] In the above [1] or [2], the catalyst contains ZnO supported on the silica carrier as the Zn, and contains Zr interacting with silanol groups of the silica carrier as the Zr.
[0011] [4] In any one of the above [1] to [3], the catalyst has a micropore volume (V micro ) is 0.03 to 0.30 cm 3 / g, and the mesopore volume (V meso ) is 0.30 to 2.0 cm 3 / g.
[0012] [5] In any one of the above [1] to [4], the catalyst has an MFI-type framework structure.
[0013] [6] In any one of the above [1] to [5], the catalyst has a molar ratio of Zn to Si, Zn / Si, of 0.001 to 0.1, and a molar ratio of Zr to Si, Zr / Si, of 0.05 to 0.5.
[0014] [7] In any one of the above [1] to [6], the catalyst is a catalyst obtained by mixing a zirconium alkoxide, an orthosilicate ester, and a first template agent together with water to prepare a zirconium silicate precursor, mixing the zirconium silicate precursor, a zinc salt, an orthosilicate ester, and a second template agent together with water, and further hydrothermally synthesizing and calcining the mixture.
[0015] [8] In the above [7], the first template agent is cetyltrimethylammonium bromide, and the second template agent is tetrapropylammonium hydroxide.
[0016] [9] In the above [7] or [8], the catalyst is obtained by the hydrothermal synthesis in the presence of a third template agent and calcination.
[0017]
[10] In the above [9], the third template agent is glycerol.
[0018]
[11] A method for producing a catalyst for synthesizing 1,3-butadiene from ethanol, the method comprising: (i) mixing a zirconium alkoxide, an orthosilicate ester, and a first template agent for forming mesopores together with water to prepare a zirconium silicate precursor; (ii) mixing the zirconium silicate precursor, a zinc salt, an orthosilicate ester, and a second template agent for forming micropores together with water; (iii) performing hydrothermal synthesis using the resulting mixture; and (iv) calcining the reaction product obtained by the hydrothermal synthesis.
[0019]
[12] In the above
[11] , the first template agent is cetyltrimethylammonium bromide, and the second template agent is tetrapropylammonium hydroxide.
[0020]
[13] In the above
[11] or
[12] , a third template agent for forming macropores is added to and mixed with the mixture, and the hydrothermal synthesis is performed using the mixed solution containing the third template agent.
[0021]
[14] In the above
[13] , the third template agent is glycerol.
[0022] According to an embodiment of the present invention, 1,3-butadiene can be efficiently synthesized from ethanol.
[0023] Zn 2p spectra of the ZnZrMFI catalyst of Example 1 and pure ZnO 2 Graph showing XRD measurement results of the ZnZrMFI catalyst of Example 1 Graph showing pore size distribution of the catalyst of Example 1 Graph showing pore size distribution of the catalyst of Comparative Example 3 Graph showing pore size distribution of the catalyst of Comparative Example 3 and pure ZrO 2 Schematic diagram of the reactor used in the examples. Graph showing the stability test results of the catalyst in Example 1.
[0024] The catalyst for synthesizing 1,3-butadiene according to this embodiment (hereinafter, sometimes simply referred to as the catalyst) and the method for producing 1,3-butadiene using the catalyst will be described below.
[0025] [Catalyst for synthesizing 1,3-butadiene] The catalyst according to the embodiment is a catalyst for synthesizing 1,3-butadiene from ethanol, and contains a porous silica support, Zn, and Zr.
[0026] Silica supports are porous crystals made of crystalline silica and have a three-dimensional pore structure. Therefore, compared to structures made of amorphous silica, they have a larger specific surface area, which is advantageous for dispersing various active centers and can improve catalytic performance. Pores include micropores, mesopores, and macropores. In one embodiment, the silica support has micropores, mesopores, and / or macropores. In this specification, micropores refer to pores with a pore diameter of 2 nm or less. Mesopores refer to pores with a pore diameter of more than 2 nm and less than 50 nm. Macropores refer to pores with a pore diameter of 50 nm or more.
[0027] The silica support is SiO 2 The skeleton structure basically contains SiO 2 However, a part of the Si contained in the framework structure may be substituted with a trivalent, tetravalent and / or pentavalent element such as aluminum. Preferably, the silica support is SiO 2 In one embodiment, the silica support may be a zeolite that does not contain aluminum element (i.e., a dealuminated zeolite).
[0028] The skeletal structure of the silica carrier is not particularly limited, and examples thereof include MFI type, BEA type, FER type, MWW type, MOR type, FAU type, LTA type, LTL type, etc., and the silica carrier may have a skeletal structure of any one of these or a combination of two or more of these. Among these, the silica carrier in one embodiment preferably has an MFI type skeletal structure.
[0029] In the catalyst, zinc (Zn) is supported on the silica support in the form of an oxide, i.e., ZnO. Because the atomic radius of Zn is larger than that of Si, Zn does not enter the framework of the silica support during the catalyst synthesis process, and is supported on the silica support in the form of an oxide. It is believed that the ZnO supported on the silica support primarily promotes the dehydrogenation of ethanol.
[0030] In the above catalyst, zirconium (Zr) is contained in a state where it mainly interacts with the silanol groups (Si-OH) of the silica support. Because the atomic radius of Zr is larger than that of Si, Zr does not enter the framework structure of the silica support during the catalyst synthesis process, and instead interacts with Zr and SiO 2 The silanol groups on the surface interact with Zr to form Lewis active centers. Here, the interaction between the silanol groups and Zr means that some kind of bond is formed between the silanol groups and Zr. Specifically, it is preferable that Zr is coordinated to the silanol groups, and Zr forms a Si-O-Zr bond together with the Si of the silanol groups, for example, in the form shown in the following formula (1), i.e., Zr(OH)(OSi) 3 You can also take.
[0031] In the above catalyst, Zr may be only one that has interacted with the silanol group in this way, but some Zr may be in the form of an oxide, i.e., ZrO 2 In one embodiment of the catalyst, Zr may be supported on a silica support in the form of Zr(OH)(OSi) 3 and ZrO 2 It may be included in the form of
[0032] The catalyst according to this embodiment has a first peak pore diameter (D micro ) and a second peak pore diameter (D meso+macro The peak pore size distribution has a multi-peak including a peak pore size distribution. The peak pore size refers to the pore size at which the distribution curve in the pore size distribution has a maximum value, and refers to the pore size at the peak of the mountain in the distribution curve. In the catalyst according to this embodiment, the boundary is 2 nm, and the peak pore size is on both sides of the boundary, and the peak pore size of 2 nm or less is called the first peak pore size (D micro ), and the peak pore diameter larger than 2 nm is called the second peak pore diameter (D meso+macro ) Such a multimodal pore size distribution is due to the catalyst having a structure including micropores as well as mesopores and / or macropores (hereinafter also referred to as a hierarchical structure), and more preferably, the catalyst has a hierarchical structure including micropores, mesopores, and macropores. The hierarchical structure improves mass transfer efficiency and resistance to carbon deposition, thereby increasing the stability of the catalyst.
[0033] D micro is not particularly limited as long as it is 2 nm or less as described above, but is preferably 0.2 nm or more and 1.5 nm or less, more preferably 0.3 nm or more and 1.0 nm or less, and even more preferably 0.4 nm or more and 0.8 nm or less.
[0034] D meso+macro is not particularly limited as long as it is greater than 2 nm as described above, but is preferably 5 nm or more and 1000 nm or less, more preferably 10 nm or more and 500 nm or less, even more preferably 20 nm or more and 300 nm or less, and even more preferably 30 nm or more and 100 nm or less.
[0035] In the above catalyst, the micropore volume (V micro ) is 0.03 to 0.30 cm 3 / g, and the mesopore volume (V meso ) is 0.30 to 2.0 cm 3 / g. micro ) and mesopore volume (V meso ) can further enhance the effect achieved by having the hierarchical structure.
[0036] V micro is more preferably 0.04 to 0.20 cm 3 / g, and more preferably 0.05 to 0.10 cm 3 / g. V meso is more preferably 0.40 to 1.0 cm 3 / g, and more preferably 0.50 to 0.80 cm 3 / g.
[0037] In the above catalyst, the molar ratio of zinc to silica, Zn / Si, is not particularly limited, but is preferably 0.001 to 0.1. A molar ratio of Zn / Si of 0.001 or more can enhance the effect of promoting ethanol dehydrogenation. A molar ratio of Zn / Si of 0.1 or less can promote ethanol dehydrogenation without inhibiting the activity of other active species. The molar ratio Zn / Si is preferably 0.005 or more, more preferably 0.008 or more. Furthermore, the molar ratio Zn / Si is preferably 0.05 or less, more preferably 0.03 or less.
[0038] In the catalyst, the molar ratio Zr / Si of zirconium element to silica element is not particularly limited, but is preferably 0.05 to 0.5. When the molar ratio Zr / Si is 0.05 or more, the effect of promoting aldol condensation and MPV reduction can be enhanced. When the molar ratio Zr / Si is 0.5 or less, the generation of by-products can be suppressed. The molar ratio Zr / Si is preferably 0.08 or more, more preferably 0.1 or more. Furthermore, the molar ratio Zr / Si is preferably 0.4 or less, more preferably 0.3 or less.
[0039] [Method for Producing Catalyst for 1,3-Butadiene Synthesis] The method for producing the catalyst is not particularly limited, but it is preferably prepared by a hydrothermal synthesis method, more preferably by a one-pot hydrothermal synthesis method.
[0040] A preferred embodiment of a production method using hydrothermal synthesis includes the following steps: (i) mixing a zirconium alkoxide, an orthosilicate ester, and a first template agent for forming mesopores together with water to prepare a zirconium silicate precursor, (ii) mixing the zirconium silicate precursor, a zinc salt, an orthosilicate ester, and a second template agent for forming micropores together with water, (iii) performing hydrothermal synthesis using the resulting mixture, and (iv) calcining the reaction product obtained by the hydrothermal synthesis.
[0041] The manufacturing method including steps (i) to (iv) above allows the synthesis of multifunctional catalysts with various active centers, such as dehydrogenation sites, Lewis acid sites, and mild Brønsted sites, in a single step. Furthermore, the active centers can be uniformly dispersed, thereby promoting interactions between the active centers. Furthermore, catalysts with a hierarchical structure can be synthesized, and in particular, Zr can interact with silanol groups on the silica surface within the hierarchical pores to form Lewis active centers.
[0042] Examples of the orthosilicate ester used as the silica source in steps (i) and (ii) include tetraethoxysilane (TEOS), tetramethoxysilane (TEMOS), tetrapropoxysilane, and tetrabutoxysilane, and these may be used alone or in combination of two or more.
[0043] The zirconium alkoxide is not particularly limited, and examples thereof include zirconium methoxide, zirconium ethoxide, zirconium propoxide, and zirconium butoxide, and these may be used alone or in combination of two or more.
[0044] The first template agent is not particularly limited as long as it is a template agent that can form mesopores, but it is preferable to use cetyltrimethylammonium bromide (CTAB).
[0045] The zinc salt is not particularly limited, and examples thereof include water-soluble zinc salts such as zinc acetate, zinc nitrate, zinc sulfate, zinc chloride, and zinc bromide, and these may be used alone or in combination of two or more.
[0046] The second template agent is not particularly limited as long as it is a template agent that can form micropores, but it is preferable to use, for example, tetrapropylammonium hydroxide (TPAOH).
[0047] Step (i) is a step of synthesizing a zirconium silicate precursor. In the presence of a first template agent for mesopore formation, an orthosilicate ester and a zirconium alkoxide are hydrolyzed to synthesize a mesoporous precursor. In step (i), when the zirconium alkoxide, the orthosilicate ester, the first template agent, and water are mixed, other components such as lower alcohols may be added. In step (i), the zirconium silicate precursor is not calcined.
[0048] Specifically, in step (i), a zirconium alkoxide and an orthosilicate ester may be dissolved in a lower alcohol such as ethanol, the resulting solution may be mixed with a first template agent and water, and the resulting first mixture may be aged. During aging, in the presence of the first template agent, the orthosilicate ester undergoes hydrolysis and dehydration condensation, and the zirconium alkoxide is hydrolyzed, causing Zr to interact with silanol groups to produce a mesoporous precursor. The resulting mixture is then centrifuged and dried to obtain a powder of the zirconium silicate precursor.
[0049] The amount of the orthosilicate ester used in step (i) is not particularly limited, but is preferably 30 to 70 mass%, more preferably 40 to 60 mass%, based on the total amount of the orthosilicate esters used in steps (i) and (ii).
[0050] The amount of zirconium alkoxide used is not particularly limited, but the molar ratio of zirconium element to silicon element, Zr / Si, relative to the total amount of orthosilicate ester used in steps (i) and (ii) is preferably 0.05 to 0.5, more preferably 0.08 to 0.4, and even more preferably 0.1 to 0.3.
[0051] The amount of the first template agent used is not particularly limited, but may be 10 to 80 parts by mass or 20 to 40 parts by mass relative to 100 parts by mass of the total amount of the orthosilicate esters used in steps (i) and (ii).
[0052] In step (ii), a second precursor is synthesized using the zirconium silicate precursor obtained in step (i) by adding an additional silica source together with a second template agent.
[0053] Specifically, in step (ii), a zinc salt and an orthosilicate ester may be dissolved in a lower alcohol such as ethanol, and the zirconium silicate precursor may be added and mixed, and the second template agent and water may be added to the resulting mixture, followed by mixing. As a result, in the presence of the zinc salt, the zirconium silicate precursor, and the second template agent, the orthosilicate ester undergoes hydrolysis and dehydration condensation to produce a ZnZr silicate precursor.
[0054] The amount of zinc salt used is not particularly limited, but the molar ratio of zinc element to silicon element, Zn / Si, relative to the total amount of orthosilicate ester used in steps (i) and (ii) is preferably 0.001 to 0.1, more preferably 0.005 to 0.05, and even more preferably 0.008 to 0.03.
[0055] The amount of the second template agent used is not particularly limited, but may be 50 to 130 parts by mass or 80 to 100 parts by mass relative to 100 parts by mass of the total amount of the orthosilicate esters used in steps (i) and (ii).
[0056] In step (ii), the lower alcohol may be distilled off from the mixture containing the ZnZr silicate precursor thus obtained.
[0057] The hydrothermal synthesis in step (iii) may be carried out immediately thereafter, or a third template agent may be added before the hydrothermal synthesis. That is, in one embodiment, a third template agent for forming macropores may be added to a mixture containing the ZnZr silicate precursor, and the hydrothermal synthesis in step (iii) may be carried out using the mixture containing the third template agent. Adding the third template agent can form larger macropores.
[0058] The third template agent is not particularly limited as long as it can form macropores, but it is preferable to use, for example, glycerol. In hydrothermal synthesis in the presence of glycerol, the particle size of the catalyst can be significantly reduced, which is advantageous for improving mass transfer efficiency.
[0059] The amount of the third template agent used is not particularly limited, but may be 10 to 80 parts by mass or 30 to 50 parts by mass relative to 100 parts by mass of the total amount of the orthosilicate esters used in steps (i) and (ii).
[0060] In step (iii), hydrothermal synthesis is performed using the mixture obtained in step (ii). Hydrothermal synthesis is a reaction carried out in the presence of high-temperature, high-pressure hot water, where further dehydration condensation occurs to produce silica. The presence of the first and second template agents (and preferably a third template agent) results in the formation of pores with corresponding pore sizes, forming a hierarchical structure. Furthermore, because one-pod hydrothermal synthesis is performed, the active centers Zn and Zr can be uniformly dispersed in the silica support, promoting interaction between the active centers.
[0061] The hydrothermal synthesis can be carried out, for example, using an autoclave. The treatment conditions are not particularly limited, but may be, for example, 150 to 180°C, under pressure that spontaneously develops with volume expansion, and for 24 to 96 hours.
[0062] After the hydrothermal synthesis, the resulting reaction product is dried, and then in step (iv), the reaction product is calcined. This results in a catalyst according to one embodiment. The calcination temperature is not particularly limited and may be, for example, 300 to 700°C or 400 to 600°C. After calcination, the product may be crushed and further molded, such as by sieving, if necessary.
[0063] [Method for Producing 1,3-Butadiene] The method for producing 1,3-butadiene according to this embodiment includes obtaining 1,3-butadiene from ethanol in the presence of the catalyst according to this embodiment described above. To achieve this, a raw material containing ethanol is brought into contact with the catalyst.
[0064] The synthetic pathway from ethanol to 1,3-butadiene using this catalyst is not particularly limited, but is generally believed to proceed as follows: (1) ethanol is dehydrogenated to acetaldehyde, (2) acetaldehyde is converted to acetaldol by aldol condensation, (3) acetaldol is converted to crotonaldehyde by dehydration, (4) crotonaldehyde is reduced together with ethanol by MPV reduction to crotyl alcohol, and (5) crotyl alcohol is dehydrated to 1,3-butadiene.
[0065] The ethanol used in the production is not particularly limited, and may be, for example, bioethanol produced from biomass or ethanol synthesized by the hydration reaction of ethylene derived from fossil fuels. The raw material may contain other components such as acetaldehyde in addition to ethanol.
[0066] The method for contacting the ethanol-containing raw material with the catalyst is not particularly limited as long as it is a method that can convert ethanol into 1,3-butadiene in the presence of the catalyst, and may be carried out in a gas phase or a liquid phase. Preferably, the ethanol-containing raw material is made into a gas and the gas is passed through a catalyst bed containing the catalyst to carry out the reaction in the gas phase.
[0067] When the reaction is carried out in a gas phase, the raw material gas may be supplied to the reaction system without dilution, or may be supplied after being diluted with an inert gas such as nitrogen or argon.
[0068] The reaction temperature (temperature of the catalyst bed) is not particularly limited as long as it is a temperature at which ethanol can be converted into 1,3-butadiene, and may be, for example, 250 to 500° C. or 300 to 400° C. The reaction pressure is also not particularly limited, and may be, for example, atmospheric pressure to 1 MPa.
[0069] The reaction method may be a continuous flow method or a batch method. In the case of a continuous flow method, the weight hourly space velocity (WHSV), which is the ratio of the raw material supply rate (weight / hour) to the catalyst weight, is not particularly limited, and may be, for example, 0.1 to 10 h -1 Or 0.3 to 2 hours -1 That's fine too.
[0070] The reaction system is not particularly limited and may be any of a fixed bed system, a moving bed system, and a fluidized bed system. The type of reactor is also not particularly limited and, for example, a tubular reactor can be used.
[0071] The product obtained after the reaction may be purified by distillation or the like, if necessary, to remove unreacted ethanol and by-products such as ethylene, ether, and acetaldehyde.
[0072] Examples will be shown below, but the present invention is not limited to these examples.
[0073] Example 1: Preparation of ZnZrMFI catalyst. 2.60 g of tetraethoxysilane (TEOS) and 2.40 g of zirconium butoxide (Zr(OBu)) were dissolved in 10 mL of ethanol. 4 The resulting solution was added to an aqueous solution of 1.91 g of cetyltrimethylammonium bromide (CTAB) in 300 mL of water and aged overnight. The mixture was then centrifuged and dried at 100°C for 12 hours to obtain a zirconium silicate precursor.
[0074] In 10 mL of ethanol, 0.05 g of zinc acetate (Zn(CH 3 COO) 2 ・2H 2 0) and 2.61 g of TEOS were added and stirred for 1 hour to dissolve. 1.00 g of zirconium silicate precursor was added and stirred for 1 hour, after which 5.08 g of tetrapropylammonium hydroxide (TPAOH) and 18.69 g of water were added and stirred for 4 hours. The resulting mixture was heated at 90°C for 4 hours to distill off the ethanol, after which 2.30 g of glycerol was added and mixed. The mixture was then transferred to a stainless steel autoclave lined with fluororesin and subjected to a hydrothermal synthesis reaction at 130°C under spontaneous pressure due to volume expansion for 48 hours. The resulting reaction product was dried at 100°C for 12 hours and then calcined in air at 550°C for 5 hours to obtain a ZnZrMFI catalyst (molar ratio Zn / Si = 0.01, molar ratio Zr / Si = 0.2).
[0075] The obtained ZnZrMFI catalyst was subjected to X-ray photoelectron spectroscopy (XPS) analysis using an "ESCALAB 250 Crossy" apparatus manufactured by Thermo Fisher Scientific, with an AlKa X-ray source. This resulted in the Zn 2p spectrum shown in Figure 1 and the Zr 3d spectrum shown in Figure 2. Furthermore, the ZnZrMFI catalyst was subjected to X-ray diffraction (XRD) analysis (CuKα 40 kV, 20 mA, 6°-60°) to obtain the measurement results shown in Figure 3.
[0076] Regarding the binding energy of the Zr 3d peak shown in Figure 2, pure ZrO 2 On the other hand, two peaks were observed for the ZnZrMFI catalyst (Zn 0.01 Zr 0.2 In the MFI, the binding energy of the Zr 3d peak is 2 The graph shows that the Zr and silanol groups interacted to form Si—O—Zr bonds. 0.01 Zr 0.2 The Zr 3d spectrum for MFI(mi) was calculated using pure ZrO 2 The catalyst of Comparative Example 3 has two main peaks corresponding to Si—O—Zr and ZrO 2 From this, it can be seen that the synthesis method using the zirconium silicate precursor according to Example 1 can further strengthen the interaction between Zr and silanol groups, and ZrO 2 It can be seen that the generation of can be further suppressed.
[0077] The binding energy of the Zn 2p peak shown in Figure 1 is 0.01 Zr 0.2 MFI) showed no obvious change in peaks compared to pure ZnO, indicating that it exists in the form of ZnO.
[0078] As shown in FIG. 3, the ZnZrMFI catalyst (Zn 0.01 Zr 0.2 MFI) has a peak characteristic of MFI indicated by an "x".
[0079] From the above, the prepared ZnZrMFI catalyst contains a silica support having an MFI-type framework structure, in which Zn is supported on the silica support in the form of ZnO and Zr is supported in the form of Zr(OH)(OSi). 3 It can be seen that it is included in the form of
[0080] Comparative Example 1: Preparation of ZnCe / beta catalyst 100 mL of 13 mol / L nitric acid was added to 5.0 g of H-beta (Tosoh Corporation's "941HOA"), and the mixture was stirred at 100°C for 12 hours, filtered, and washed to obtain Si-beta. 5 g of Si-beta and 0.96 g of Zn(NO 3 ) 2 ・6H 2 O and 0.66 g of Ce(NO 3 ) 3 ・6H 2 O was mixed and finely pulverized, and then calcined in air at 500° C. for 6 hours, thereby obtaining a ZnCe / beta catalyst (Zn content=5.0 mass %, Ce content=5.0 mass %).
[0081] Comparative Example 2: Preparation of ZrMFI catalyst 1.91 g of CTAB was dissolved in 300 mL of deionized water with stirring to obtain solution A. 2.60 g of TEOS and 2.40 g of Zr(OBu) 4 was mixed with 10 mL of ethanol under stirring to obtain solution B. Solution B was slowly added to solution A with stirring and aged overnight. The solid product was centrifuged at 2500 rpm and dried at 60°C overnight to obtain a zirconium silicate precursor.
[0082] A mixed solution was prepared by adding 2.60 g of TEOS to 10 mL of ethanol. The zirconium silicate precursor was added to the mixed solution and stirred for 1 hour. Next, 5.08 g of TPAOH and 18.69 g of H 2The mixture was stirred at 700 rpm for 4 hours and then heated at 90°C for 4 hours to remove most of the water and ethanol from the mixture. After forming a gel, it was mixed with 2.30 g of glycerol and then transferred to a stainless steel autoclave lined with fluororesin for hydrothermal synthesis at 130°C for 48 hours. The product was dried at 100°C for 12 hours and then calcined in air at 550°C for 5 hours to obtain Zr. 0.2 An MFI catalyst was obtained.
[0083] Comparative Example 3: Preparation of ZnZrMFI(mi) catalyst. 3 COO) 2 ・2H 2 0 and 5.21 g of TEOS were added and stirred for 1 hour to dissolve. 4 After adding the above and stirring for 1 hour, 5.08 g of TPAOH and 18.69 g of water were added and stirred for 4 hours. The resulting mixture was heated at 90°C for 4 hours to remove the ethanol, and then transferred to a stainless steel autoclave lined with fluororesin and subjected to a hydrothermal synthesis reaction at 130°C for 48 hours under pressure generated spontaneously by volume expansion. The resulting reaction product was dried at 100°C for 12 hours and then calcined in air at 550°C for 5 hours to obtain a ZnZrMFI(mi) catalyst (molar ratio Zn / Si = 0.01, molar ratio Zr / Si = 0.2).
[0084] [Measurement of pore diameter and pore volume] The pore diameters of the ZnZrMFI catalyst of Example 1 and the ZnZrMFI(mi) catalyst of Comparative Example 3 were measured, and the peak pore diameter (D micro , D meso+macro ) was determined. In addition, the micropore volume (V micro ) and mesopore volume (V meso The measurement method is as follows.
[0085] The catalyst was used as a sample, and nitrogen (N 2 Before the measurement, the sample was degassed in a vacuum at 350°C for 5 hours.
[0086] This measuring device analyzes the pore size distribution of micropores by the HK method, and the pore size distribution of mesopores and macropores by the BJH method. The pore size distribution of the log differential pore volume distribution (dV / dlogD) was obtained by the measurement. As shown in Figure 4, this pore size distribution has the pore size on the horizontal axis and the pore size on the vertical axis. dV / dlogD is the value obtained by dividing the differential pore volume dV by the logarithmic difference value d (logD) of the pore size, and this is plotted against the average pore size for each interval. From the obtained pore size distribution, the peak pore size of the micropores (D micro ) and the peak pore diameter of mesopores and macropores (D meso+macro ) was sought.
[0087] In addition, the micropore volume (V micro ) was calculated by the BJH method, and the mesopore volume (V meso ) was calculated.
[0088] The pore size distributions of the catalysts of Example 1 and Comparative Example 3 are shown in Figures 4 and 5, respectively. As shown in Figure 5, the catalyst of Comparative Example 3 had a pore size distribution of D micro In contrast, the catalyst of Example 1 had a single peak pore diameter of D = 0.54 nm, as shown in FIG. micro = 0.55 nm and D meso+macro The catalyst of Example 1 had two peak pore diameters of 50.18 nm and 50.18 nm, and thus had a multimodal pore size distribution. The catalyst of Example 1 also had micropores with a pore diameter of 2 nm or less, mesopores with a pore diameter of more than 2 nm and less than 50 nm, and macropores with a pore diameter of 50 nm or more, and thus had hierarchical nano-sized pores.
[0089] Furthermore, as shown in Table 1 below, the catalyst of Example 1 has a larger mesopore volume V than the catalyst of Comparative Example 3. meso is large, and the micropore volume V micro The total pore volume V total It was also big.
[0090] [Catalytic Performance Evaluation Test] Each of the catalysts prepared above was subjected to a catalytic performance evaluation test in a synthesis reaction of 1,3-butadiene from ethanol. The synthesis reaction was carried out under atmospheric pressure using a quartz fixed-bed flow reactor with an inner diameter of 4 mm.
[0091] A conceptual diagram of the reaction apparatus is shown in Figure 7. In Figure 7, reference numeral 12 denotes a nitrogen cylinder that supplies nitrogen as a carrier gas, reference numeral 14 denotes a syringe pump that supplies ethanol, reference numeral 16 denotes a mass flow controller (MFC), reference numeral 18 denotes an evaporator, and reference numeral 20 denotes a ribbon heater as a line heater that heats the outer periphery of a pipe through which the gas flows.
[0092] Reference numeral 22 denotes a fixed-bed flow-type reactor, reference numeral 24 denotes a catalyst bed in the reactor 22, reference numeral 26 denotes an electric furnace that heats the reactor 22, and reference numeral 28 denotes a thermocouple thermometer (TC) that detects the temperature of the catalyst bed 24.
[0093] Reference numeral 30 denotes a pipe through which gas that has passed through the reactor 22 flows, reference numeral 32 denotes a bypass route that bypasses the reactor 22, reference numeral 34 denotes a gas chromatograph (GC) for analyzing the gas product, reference numeral 36 denotes an exhaust gas outlet, and reference numeral 38 denotes a six-way valve for switching the flow path for the above-mentioned pipe 30, bypass route 32, GC 34, and exhaust gas outlet 36.
[0094] The reactor 22 was filled with 0.5 g of catalyst to form a catalyst bed 24, and quartz wool 40 was packed and fixed on both sides of the catalyst bed 24. Nitrogen was flowed into the reactor 22 from the nitrogen cylinder 12 via the MFC 16 at a flow rate of 20 mL / min, and the reactor was pretreated at 400°C for 1 hour. After cooling to 350°C, ethanol was introduced into the reaction system using the syringe pump 14 at a rate of 0.24 mL / h (diluted by flowing nitrogen as a carrier gas at 20 mL / min) (WHSV = 0.38 h). -1 The catalyst was evaluated for 6 hours.
[0095] On-line, the gas product discharged from the reactor 22 was introduced into a gas chromatograph (GC) 34, and the gas product was analyzed using a gas chromatograph (Shimadzu GC-14B manufactured by Shimadzu Corporation and DB-1 column (30 m × 0.25 mm × 0.25 μm) manufactured by GL Sciences) and a flame ionization detector (FID).
[0096] The formulas for calculating the conversion rate (ethanol conversion rate), the selectivity of each product, and the yield (yield of 1,3-butadiene) are shown below.
[0097]
[0098] The results are shown in Table 1, and 1,3-butadiene, ethylene, acetaldehyde, diethyl ether, and other coupling products were detected. With the catalyst of Example 1, the ethanol conversion rate was significantly higher and the yield of 1,3-butadiene was significantly improved compared to the ZnCe / beta catalyst of Comparative Example 1 and the ZnMFI catalyst of Comparative Example 2. Furthermore, compared to Comparative Example 3, which used a ZnZrMFI(mi) catalyst without a hierarchical structure, the selectivity of 1,3-butadiene was significantly higher and the yield of 1,3-butadiene was also significantly improved. Therefore, Example 1 enabled efficient synthesis of 1,3-butadiene.
[0099] [Catalyst Stability Test] In the catalyst stability test, the catalyst performance evaluation test was carried out for 80 hours on the catalyst of Example 1, and the conversion rate (Ethanol conv.) and 1,3-butadiene selectivity (Butadiene sel.) were measured every hour during the day.
[0100] The results are shown in FIG. 8, and the catalyst of Example 1 was found to be excellent in stability.
[0101] The various numerical ranges described in this specification can be arbitrarily combined with their respective upper and lower limit values, and all such combinations are considered to be preferred numerical ranges described in this specification. Furthermore, a numerical range described as "X to Y" means from X to Y.
[0102] Although several embodiments of the present invention have been described above, these embodiments are presented as examples and are not intended to limit the scope of the invention. These embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their omissions, substitutions, modifications, etc. are included within the scope and spirit of the invention, as well as within the scope of the invention described in the claims and their equivalents.
Claims
1. A catalyst for synthesizing 1,3-butadiene from ethanol, comprising a porous silica carrier composed of crystalline silica, Zn, and Zr, having a multimodal pore size distribution including a first peak pore diameter (D micro ) of 2 nm or less and a second peak pore diameter (D meso+macro ) of more than 2 nm, the catalyst for 1,3-butadiene synthesis.
2. The catalyst for 1,3-butadiene synthesis according to claim 1, which contains ZnO supported on the silica carrier as the Zn and contains Zr interacting with the silanol groups of the silica carrier as the Zr.
3. The micropore volume (V micro ) calculated by the t-plot method is 0.03 to 0.30 cm 3 / g, and the mesopore volume (V meso ) calculated by the BJH method is 0.30 to 2.0 cm 3 / g. The catalyst for 1,3-butadiene synthesis according to claim 1 or 2.
4. The catalyst for 1,3-butadiene synthesis according to any one of claims 1 to 3, wherein the silica carrier has an MFI-type framework structure.
5. The catalyst for 1,3-butadiene synthesis according to any one of claims 1 to 4, wherein the molar ratio of Zn to Si, Zn / Si, is 0.001 to 0.1, and the molar ratio of Zr to Si, Zr / Si, is 0.05 to 0.
5.
6. The catalyst for 1,3-butadiene synthesis according to any one of claims 1 to 5, which is obtained by mixing a zirconium alkoxide, an orthosilicate ester, and a first template agent with water to prepare a zirconium silicate precursor, mixing the zirconium silicate precursor, a zinc salt, an orthosilicate ester, and a second template agent with water, and further performing hydrothermal synthesis and calcination.
7. The catalyst for 1,3-butadiene synthesis according to claim 6, wherein the first template agent is cetyltrimethylammonium bromide and the second template agent is tetrapropylammonium hydroxide.
8. The catalyst for 1,3-butadiene synthesis according to claim 6 or 7, which is obtained by performing the hydrothermal synthesis and calcination in the presence of a third template agent.
9. The catalyst for 1,3-butadiene synthesis according to claim 8, wherein the third template agent is glycerol.
10. A catalyst comprising a porous silica carrier composed of crystalline silica, Zn, and Zr, the catalyst having a multimodal pore size distribution including a first peak pore diameter (D micro ) of 2 nm or less and a second peak pore diameter (D meso+macro ) of more than 2 nm, the method for producing 1,3-butadiene comprising obtaining 1,3-butadiene from ethanol in the presence of the catalyst.
11. The method for producing 1,3-butadiene according to claim 10, wherein the catalyst contains ZnO supported on the silica carrier as the Zn and contains Zr interacting with the silanol groups of the silica carrier as the Zr.
12. The catalyst has a micropore volume (V micro ) calculated by the t-plot method of 0.03 to 0.30 cm 3 / g, and a mesopore volume (V meso ) calculated by the BJH method of 0.30 to 2.0 cm 3 / g. The method for producing 1,3-butadiene according to claim 10 or 11.
13. The method for producing 1,3-butadiene according to any one of claims 10 to 12, wherein the catalyst has an MFI-type framework structure for the silica carrier.
14. A method for producing a catalyst for 1,3-butadiene synthesis for synthesizing 1,3-butadiene from ethanol, comprising: preparing a zirconium silicate precursor by mixing a zirconium alkoxide, an orthosilicate ester, and a first template agent for mesopore formation with water; mixing the zirconium silicate precursor, a zinc salt, an orthosilicate ester, and a second template agent for micropore formation with water; performing hydrothermal synthesis using the obtained mixture; and firing the reaction product obtained by the hydrothermal synthesis. A method for producing a catalyst for 1,3-butadiene synthesis.
15. The method for producing a catalyst for 1,3-butadiene synthesis according to claim 14, wherein a third template agent for macropore formation is added to and mixed with the mixture, and the hydrothermal synthesis is performed using the mixed solution containing the third template agent.